Alcohol and marijuana co-use: Consequences, subjective intoxication, and the operationalization of simultaneous use. (1st July 2020) - Sokolovsky, Alexander W.; Gunn, Rachel L.; Micalizzi, Lauren; White, Helene R.; Jackson, Kristina M.
Highlights: Alcohol and marijuana are frequently used simultaneously. There is no consistent operational definition for "simultaneous" use. Competing time-based operationalizations of simultaneity were investigated. Daily co-use of alcohol and marijuana increased risk versus single-substance use. Risks of simultaneous use remains significant, regardless of operationalization. Abstract: Background: Alcohol and marijuana are frequently co-used with overlapping effects. However, the absence of consistent operational definitions delineating simultaneous alcohol and marijuana use (SAM) from concurrent use (CAM) challenges consistent inferences about these behaviors. This study first examined whether daily alcohol and marijuana co-use predicted substance-use related consequences and subjective intoxication; and then evaluated whether competing operationalizations of SAM and CAM were associated with differences in these outcomes on co-use days. Methods: A sample of 341 young adult college students who reported past-month use of both alcohol and marijuana "at the same time so that their effects overlapped" completed a two-wave survey with paired 28-day daily experience sampling bursts examining alcohol and marijuana co-use. Outcomes were (a) daily substance-use related consequences; and (b) daily subjective intoxication. Focal predictors were daily drinks and marijuana uses; daily co-use versus single-substance use (Aim 1) or CAM versus SAM (Aim 2); and their interaction. Results: Participants reported more negative consequences on co-use days versus marijuana-only days and greater subjective intoxication relative to alcohol or marijuana-only days. Competing operationalizations of SAM, defined as daily co-use occurring within 1−240 min in increments of 1 min, found no difference in consequences or subjective intoxication regardless of operationalization. Conclusion: Co-use days involve greater risk than alcohol-only or marijuana-only days. Although there was no evidence of additional daily risk from simultaneous use regardless of the timeframe used to operationalize it, investigating these effects remains challenging due to the generally small timeframe between substances on co-use days in this sample.